CONTENT STRATEGY THREE DAI FAMOUS ON INSTAGRAM - Ulfa Khairina (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2021)
The increasing number of social media users in Indonesia is not only among teenagers and technology conscious. Preachers also use social media in spreading Islam in the technology era. Social media is also used by preachers to get audiences of da’wah. Currently, there are three preachers who are active in the use of social media as a media of preaching and gained many followers on instagram; they are Ust. Felix Siauw, Ust. Abdul Somad, and Ust. Adi Hidayat. All three of them have unique and distinctive content in preaching. This study examines the strategic content used by the preachers on instagram. The object of study is analyzed content on the October 2020’s period using a descriptive qualitative approach. The method used is documentation with analysis techniques. The results of study found that UAS used instagram as a visual documentation of all dakwah activities and management of the boarding school. UAH uses instagram as contemporary PR and personal branding. Meanwhile, Felix Siauw uses instagram as a media for da’wah bil qalam through written captions for followers. These three preachers use Berlo’s communication theory, namely S-M-C-R.Keywords: social media, da’wah, instagram, famous da’i.